Futuric Sdn. Bhd. / Suci Salsabilla Mohd Hidli … [et al.] - Mohd Hidli, Suci Salsabilla; Abdillah, Nuryasyqin; Rosli, Ainnin Sofiya; Hayazi, Muhammad Afiq; Razali, Elmi Nasrun (2022)
Futuric Sdn. Bhd. or also known as FUTURIC is a product-oriented company that sells backpacks. Our company's mission is to make it easier for our customers to live peacefully and comfortably in this endemic era. Futuric Sdn. Bhd. is a futuristic and environmentally conscious company founded by former students in Melaka, Malaysia. Our company provides a backpack desk kit to improve employers' and students' lifestyles during this endemic era. With the backpack desk kit, they can bring their laptop and set up their workspace anywhere thanks to the desk extension feature that comes with the bag. Furthermore, because the desk extension is already built-in and simple to use, users can easily put it back into the bag. The company was founded by a group of former students that share their experiences adapting to the situation where we need to have class online while also attending physical class. As the problem worsens, students risk becoming emotionally exhausted while attempting to catch up on lessons. We created this new product in response to several complaints and petitions from people on social media who had previously experienced this situation. As a result, we founded Futuric Sdn. Bhd. to provide a better and solution for students and employees who faced similar issues. The business is a partnership between 5 members which are Ainnin Sofiya as Chief Executive Officer, Muhammad Afiq Hayazi as Administritive department, Elmi Nasrun as Marketing department, Nuryasyqin and Suci Salsabilla as Designer. The company targets to achieve more than RM 200,000 of sales for the first month of the operations. We also aim to make our earnings consistent and profitable.